Moral Transformation in the Johannine Writings - Bennema, Cornelis (In die Skriflig/In Luce Verbi, 2017)
Johannine ethics is a problematic area for scholarship but recently there has been a breakthrough. In this new era of Johannine ethics, the present study examines the concept of moral transformation. The argument is that the Johannine writings present a moral narrative world where a moral God saves immoral people by bringing them into his moral world. When people live in God’s moral world their character and conduct are shaped in accordance with the moral beliefs, values and norms of the divine reality. In order to model and promote the envisaged morality among his readers, John presents various characters, whose characteristics and behaviour might be either emulated or avoided.
free